2013
DOI: 10.1590/s1677-5538.ibju.2013.06.12
|View full text |Cite
|
Sign up to set email alerts
|

Study of the ureter structure in anencephalic fetuses

Abstract: Purpose: The objective of this paper is to analyze the structure of the ureter in normal and anencephalic human fetuses. Materials and Methods:We studied 16 ureters from 8 human fetuses without congenital anomalies aged 16 to 27 weeks post-conception (WPC) and 14 ureters from 7 anencephalic fetuses aged 19 to 33 WPC. The ureters were dissected and embedded in paraffin, from which 5 µm thick sections were obtained and stained with Masson trichrome, to quantify smooth muscle cells (SMC) and to determine the uret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Recently, Costa et al ( 27 ) studied 17 human fetuses with NTDs and found that urogenital anomalies in human fetuses with NTDs are significant, with an incidence greater than 20%, but did not find severe urogenital anomalies that impair body function. The same group reported that in fetuses with anencephaly, the ureters had smaller diameter, area and thickness, which could indicate that this tissue tends to have significant structural alterations, probably due to cerebral lesions with consequent brain control damage of ureter nerves ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Costa et al ( 27 ) studied 17 human fetuses with NTDs and found that urogenital anomalies in human fetuses with NTDs are significant, with an incidence greater than 20%, but did not find severe urogenital anomalies that impair body function. The same group reported that in fetuses with anencephaly, the ureters had smaller diameter, area and thickness, which could indicate that this tissue tends to have significant structural alterations, probably due to cerebral lesions with consequent brain control damage of ureter nerves ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pazos et al ( 14 ) found that the bladders of anencephalic fetuses had gross histological alterations when compared to those of normal fetuses. Costa et al ( 15 ) demonstrated differences in the structure of the ureter. Kalaycioglu et al ( 16 ) carried out a stereological evaluation of the kidneys of anencephalic and normal fetuses and found no significant differences between the groups.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the urogenital tract of anencephalic fetuses has been studied, including the kidneys and collecting system [2,3], ureters [4], bladder [5], prostate [6,7], penis [8], testicles [9], female external genitalia [10] and vagina [11]. Some authors have indicated a different response of male and female anencephalic fetuses to hormonal stimulation [12].…”
Section: Introductionmentioning
confidence: 99%